PRINCIPLES OF ECONOMIC IBN TAYMIYYAH (Moral Analysis) - Duriana, Duriana (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This paper discusses the economic principles of Ibn Taymiyyah with moral analysis. The purpose of this paper is to reveal the position of morality in economic principles of Ibn Taymiyyah. There are two issues to be answered in this paper are: how is the economic principles of Ibn Taymiyyah, and how is the moral position in the economic principles of Ibn Taymiyyah. This research was found: principles of Ibn Taymiyyahs economy include: the principle of balance, fairness, sharia, cooperation, consultation and the prohibition of usury. Moral position in the economic principles of Ibn Taymiyyah is the basis and foundation of the economy which is essentially based on justice as a moral parent intended to protect the public from a variety of exploitative actions.Â —–Tulisan ini membahas tentang prinsip-prinsip ekonomi Ibnu Taimiyah dengan analisis moral. Tujuannya adalah untuk mengungkap posisi moralitas dalam prinsip-prinsip ekonomi Ibnu Taimiyah. Terdapat dua masalah yang ingin dijawab dalam tulisan ini yaitu: 1. Bagaimana prinsip-prinsip ekonomi Ibnu Taimiyah? 2. Bagaimana posisi moral dalam prinsip-prinsip ekonomi Ibnu Taimiyah? Berdasarkan penelusuran yang dilakukan ditemukan bahwa: Prinsip-prinsip ekonomi Ibnu Taimiyah meliputi: Prinsip keseimbangan, keadilan, syariah, kerja sama, musyawarah dan larangan riba. Posisi moral dalam prinsip ekonomi Ibnu Taimiyah menjadi dasar dan pondasi ekonomi yang pada hakekatnya bertumpu pada penegakan keadilan sebagai induk moral yang bertujuan melindungi masyarakat dari berbagai tindakan eksploitatif.